Evaluation of the strength deficit after surgery intervention by the use of a maximal isometric force test and anthropometric measurement - Ferrer, V.; Roig, A.; Benquells, M.; Pons, V. (Archivos de medicina del deporte, 2008)
Even though it has been proved that big differences exist between dynamic and isometric muscular performance (Baker, et al.; 1994), the reproducibility (Heinonen, et al.; 1993) and specificity of the isometric test, turns it to an optimal system for the evaluation of the contractile capacity of the muscle, especially when the athlete cannot execute a dynamic test because of a limitation his/her movement`s amplitude (González Badillo, Gorsostiaga; 2002). Many Literature from different authors can be found about the use of this methodology for the measurement of asymmetry on bilateral strength (Impeleizzeri, et al.; 2007) and have determined that differences larger than 10 - 15% are closely related to higher predisposition to injury (Herzog, et al.; 1989 Impellizzeri, et al.; 2007; Petsching, et al.; 1998). Muscular areas can be calculated from the measurement of skin fold and muscular perimeter, and are used as an indirect indicator of the level of a segment`s hypertrophy (Banquells, et al.; 1992). The aim of this study was to evaluate the recovery level of an athlete that underwent surgery because of a patellar transverse fracture, by the use of an isometric leg press exercise test and an anthropometrical evaluation of the muscular area of the middle thigh. Method: An international level gymnast incorporated to the training routine from a medical surgery 16 months before, passed an evaluation of the leg`s strength by means of a maximal isometric leg press test with each leg separately and simultaneously. The protocol demanded to reach the maximum isometric force in the shortest time possible and to maintain it for 5 seconds. The subject performed 2 attempts, with a recovery time of 1 minute, and the one with the highest mean force value at 200ms (Hamar; 2008) was selected for the analysis. The leg press (Salter, series M487) used for this study was equipped with a load cell (AEP Transducers, model TCE). Anthropometric evaluation of the muscular area was done the same day, measuring the muscular perimeter and the anterior, internal and external skin fold of the middle thigh. Results: The athlete developed an absolute maximal isometric bilateral force of 2870N. Analyzing the unilateral attempts, a 15% deficit of isometric force was found on the operated leg, and a 12% deficit of explosive force, with respect to the non-operated leg. In the same way, an 8% deficiency of muscular area was observed on the operated leg`s middle thigh, during anthropometric evaluation. Discussion/Conclusions: The evaluation tests showed a clear deficit on isometric and explosive force and on muscular hypertrophy of the injured leg. The use of a combined protocol, mixing a maximal isometric strength test and an anthropometric evaluation, can be a useful tool for the detection of muscular deficiencies on athletes that have returned to training sessions after surgery